Gabapentin for chronic pelvic pain in women (GaPP2): a multicentre, randomised, double-blind, placebo-controlled trial - Horne, A; Vincent, K; Hewitt, C; Middleton, L; Koscielniak, M; Szubert, W; Doust, A; Daniels, J; GaPP2 collaborative (Elsevier, 2020)
Background Chronic pelvic pain affects 2–24% of women worldwide and evidence for medical treatments is scarce. Gabapentin is effective in treating some chronic pain conditions. We aimed to measure the efficacy and safety of gabapentin in women with chronic pelvic pain and no obvious pelvic pathology.